Analisis Wacana Kritis Media Online Detik.Com Berita Pengadaan Seragam LV Dewan Perwakilan Rakyat Kota Tangerang - Khotimah, Khusnul; Hidayat, Ryan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This study's problem formulation is based on van Dijk's critical discourse, which includes text, social cognition, and social environment. The descriptive qualitative research method was used in this study. In August 2021, the internet media